Evaluation of the Ecosystem Services Value of Agricultural Industrial Parks under the Background of Tianfu Granary Construction - A Case Study of the Daoming and Longxing Districts in Chongzhou City - Wang, Jiatong; Xv, Haoran; Wang, Yihong; Xie, Huan; Zhao, Ruifeng (Transactions on Economics, Business and Management Research, 2024)
In the new era, China faces two major challenges of food security and ecological protection. The agricultural industrial parks constructed in the process of developing the Tianfu Granary play a significant role in China's food supply and ecological security as a special type of farmland ecosystem. Accurately calculating the value of ecosystem services in agricultural industrial parks is of great importance for achieving sustainable agricultural development and comprehensively realizing rural revitalization. This paper takes the Daoming and Longxing Agricultural Industrial Parks in Chongzhou City as the research subjects, constructs an evaluation index system for ecosystem service value, and assesses and calculates the supply, support, regulation, and cultural services of the agricultural industrial parks. The research findings show that the total value of ecosystem services reaches 260.64 million yuan, which is 4.65 times the value of the agricultural products supplied, and its significant ecosystem service value cannot be ignored. Among the ecosystem service values of the park, the cultural service value is the highest, followed by the social security service value. Based on the above conclusions, this paper discusses how to achieve high-standard construction of agricultural industrial parks, providing a scientific basis for the government and policymakers to make correct decisions in the rational use of resources, reduce and avoid short-term economic behaviors that damage ecosystem service functions, and promote sustainable agricultural development.